(untitled) (Research, Society and Development, 2020)
Digital technology has expanded in the most varied branches, which brings the need to adapt professionals to the reality of the job market. The introduction of artificial intelligence in the practice of law results from decades of studies to optimize time and standardize procedures for harmony and administrative integration in the judiciary (Andrade, Rosa & Pinto, 2020). A question that needs to be debated in this regard is whether the exponential growth of digital technology will prove to be an opportunity or a downfall for legal professionals. Based on these questions, the objective of this study is to weave reflections on the use of artificial intelligence in the professional practice of legal activities. To answer the proposed question, a descriptive literature review on the subject and a documentary analysis of the websites of the judiciary in Brazil were carried out. In this study, about 11 examples of the use of artificial intelligence in Brazilian courts were found. The ability to analyze billions of information and establish logical connections between them, accomplished through artificial intelligence, represents a gain for the work of lawyers and the Judiciary. It happens that technological advances continue at a great speed and law schools continue to train professionals who in a short period of time can be replaced by robots. In the meantime, it is essential to think about not only changing the mentality of those who are in practice, but also reformulating the way of teaching law and approaching the profession in school benches.